2018
DOI: 10.1542/peds.2017-2675
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Effects of Parent-Child Book Reading Interventions: A Meta-analysis

Abstract: PCBR interventions are positively and significantly beneficial to the psychosocial functioning of both children and parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 77 publications
2
10
0
3
Order By: Relevance
“…Previous research has indicated that shared book reading or storytelling during regular bedtime routines is one of the components of the home literacy environment influencing children’s subsequent verbal and cognitive development (Kitsaras et al., 2018). This is in accordance with the well‐established influence of shared book reading in the promotion of children’s language and psychosocial development (Dowdall et al., 2020; Xie, Chan, Ji, & Chan, 2018). Indeed, parental reports of home literacy activities (a composite measure that included the mother’s implication in LBR) in the first years of life contributed significantly to the prediction of children’s oral language, vocabulary, and cognitive skills at ages 3 and 5 years (Rodriguez & Tamis‐LeMonda, 2011; Rodriguez et al., 2009).…”
Section: Introductionsupporting
confidence: 87%
“…Previous research has indicated that shared book reading or storytelling during regular bedtime routines is one of the components of the home literacy environment influencing children’s subsequent verbal and cognitive development (Kitsaras et al., 2018). This is in accordance with the well‐established influence of shared book reading in the promotion of children’s language and psychosocial development (Dowdall et al., 2020; Xie, Chan, Ji, & Chan, 2018). Indeed, parental reports of home literacy activities (a composite measure that included the mother’s implication in LBR) in the first years of life contributed significantly to the prediction of children’s oral language, vocabulary, and cognitive skills at ages 3 and 5 years (Rodriguez & Tamis‐LeMonda, 2011; Rodriguez et al., 2009).…”
Section: Introductionsupporting
confidence: 87%
“…A protocol was submitted to the PROSPERO registry for systematic reviews (CRD number: 42017057258) with child language as the primary outcome. While this registered protocol also specified assessment of child socioemotional outcomes as a secondary outcome, a recent meta‐analysis (Xie, Chan, Ji, & Chan, ) focused directly on this question, rendering this analysis redundant. PRISMA guidelines of reporting were followed.…”
Section: Methodsmentioning
confidence: 99%
“…As occurred with nonmobile media (defined as media not experienced on a mobile device such as printed books and television), scaffolding may create opportunities for high quality interactions, such as asking questions, labeling objects, singing and being verbally affectionate (Pempek, Demers, Hanson, Kirkorian, & Anderson, 2011). Stimulating interactions are also a vital element of a secure attachment (De Wolff & van Ijzendoorn, 1997) and such exchanges could positively impact the overall quality of parent–child relationships (Xie, Chan, Ji, & Chan, 2018). They may have additional developmental and literacy benefits (Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991; Weizman & Snow, 2001).…”
Section: Introductionmentioning
confidence: 99%